Exploring the Potentials of Laser Induced Forward Transfer and Laser Annealing Processes for Synthesis/Printing of Silver Nanofilms on Quartz Substrates using Nd:YAG and CO2 Laser Beams - Hanadi H. Altawil (مجلة النهرين للعلوم الهندسية, 2024)
Laser annealing represents a powerful method for tailoring the properties of silver nanofilms on quartz substrates, offering advantages in terms of precision, scalability, and functionalization. Continued research efforts are expected to deepen our understanding and broaden the applications of this promising technology in diverse fields. In this work, laser annealing of silver nanofilms deposited on quartz substrates was performed and investigated. RF CO2 laser of variable power in the range 1–20 W with beam quality of 1.1 was used to anneal silver nanofilms. AFM analysis emphasized that nanocrystal sizes of 60 nm were obtained for silver nanofilms. Furthermore, the optimum absorbance peak occurred at about 449 nm for smaller film thickness. Thermal simulation and analysis of the annealing process were also conducted using COMSOL Multiphysics software. It was observed that optimal temperature of 729 K was achieved when 10 W laser power and 2 mm/s scanning speed were used to anneal 20 nm silver film thickness. Design of expert analysis was also used to better understand the laser annealing process of silver nanofilms since convolution of several process parameters affect the process output.